Quantitative phosphoproteomics to resolve the cellular responses to octanoic acid in rotenone exposed zebrafish - ALTURFAN, EBRU IŞIK (WILEY, 2021)
Ketosis is a potentially beneficial metabolic state for health especially in neurological conditions including Parkinson's disease (PD). Medium-chain-triglycerides (MCT) have specific metabolic properties and they are described as ketogenic even without restriction of carbohydrate. Octanoic acid (C8) is the main MCT showing this effect. Rotenone is a neurotoxin that is used to induce experimental PD model. Rotenone inhibits mitochondrial respiratory complex 1 (MRC1) and causes reactive oxygen species formation. Mass spectrometry (MS)-based phosphoproteomic methods enable discovering specific signaling events in special molecular pathways through identification and quantification of phosphoproteins. Signaling networks involved in rotenone-mediated biological processes and beneficial effects of MCTs on neurodegenerative diseases are not well understood. We aimed to gain comprehensive molecular perspective on the global phosphoproteome differences in rotenone-exposed zebrafish treated with octanoic acid. Raw files obtained from MS analysis were processed and searched against the Danio rerio protein database using SEQUEST-HT algorithm to identify and quantify phosphopeptides with 2,569 unique phosphoproteins and 4,161 unique phosphopeptides corresponding to 2005 proteins. Microtubule-associated protein (MAP) family members were significantly lower in rotenone group. Phosphoproteins involved in ion binding (calcium, magnesium, zinc ion), oxygen binding, microtubule binding, ATP- and GTP-binding were among differentially expressed 347 proteins in rotenone group and they were reversed after octanoic acid treatments. Phosphoproteins and phosphorylation sites were identified for future exploration of signaling pathways involved in rotenone toxicity. We believe our findings might help in the formulation of effective therapeutic strategies for the treatment of PD using ketogenic formulations involving MCTs. Practical applications Ketosis is a potentially beneficial metabolic state for health especially in neurological conditions including Parkinson's disease (PD). Medium-chain-triglycerides (MCT) (C6-C12) have specific metabolic properties making them described as ketogenic even without restriction of carbohydrate. Octanoic acid (caprylic acid, C8) is the main MCT showing this effect. Our findings might help in the formulation of effective therapeutic strategies for the treatment of Parkinson's disease using ketogenic formulations involving Medium-chain-triglycerides.
Keywords: ketosis; octanoic acid; Parkinson's disease; phosphoproteome; zebrafish; TAU-PHOSPHORYLATION; LEWY BODIES; MITOCHONDRIA; CONTRIBUTES; DYNAMICS; PROTEIN; BRAIN